Physical, social, and emotional impact on patients with congenital heart disease undergoing cardiac catheterization - Maricel Licht-Ardila; Alexandra Hurtado-Ortiz; Edgar Fabián Manrique-Hernández; Justo José Santiago Peña (Anales de Pediatría (English Edition))
Introduction: The management of congenital heart disease (CHD) has evolved, improving patient outcomes; however, challenges persist for patients, emphasizing the importance of assessing health-related quality of life (HRQoL). The widely used Pediatric Quality of Life Inventory underscores the relevance of HRQoL assessment, especially in children subject to medical procedures. Objective: To evaluate HRQoL in children with congenital heart disease undergoing cardiac catheterization, analysing its association with clinical and sociodemographic variables in a tertiary care hospital. Materials and methods: We conducted a cross-sectional study in paediatric patients aged 2–18 years undergoing haemodynamic procedures for congenital heart diseases. We used the Pediatric Quality of Life Inventory (PedsQL) to assess HRQoL. The statistical analysis included descriptive statistics, χ2 tests, Kruskal–Wallis tests and multivariate linear regression analysis with the aim of identifying factors associated with HRQoL. Results: The sample included 164 patients, among whom pulmonary atresia and patent ductus arteriosus were frequent diagnoses. Physical functioning and school functioning were significantly impaired, with median scores of 32.14 (IQR, 17.14–62.87) and 56 (IQR, 28–88), respectively. The results were more favourable for emotional functioning and social functioning, with median scores of 62 (IQR, 32–74) and 68 (IQR, 44–100), respectively. Single ventricle defects and pulmonary atresia were associated with lower quality of life scores in emotional functioning (P = .035) and physical functioning (P = .048), respectively. Conclusion: This study highlights the current challenges in evaluating HRQoL for children with CHD. It identified significant associations between specific diagnoses and decreased HRQoL scores, emphasizing the need for comprehensive care strategies. Resumen: Introducción: El manejo de la cardiopatía congénita (CC) ha evolucionado, mejorando el pronóstico, pero persisten desafíos para los pacientes, subrayando la importancia de evaluar la calidad de vida relacionada con la salud (CVRS). El cuestionario de calidad de vida pediátrica PedsQL, ampliamente utilizado, resalta la relevancia de la evaluación de CVRS, especialmente en niños sometidos a intervenciones médicas. Objetivo: Evaluar la CVRS de niños con cardiopatía congénita sometidos a cateterismo cardíaco, examinando su relación con variables clínicas y sociodemográficas en una institución de alta complejidad. Materiales y métodos: Se llevó a cabo un estudio transversal en pacientes pediátricos de 2 a 18 años sometidos a cateterismo para patologías congénitas. Se utilizó el cuestionario de calidad de vida pediátrica PedsQL para evaluar la CVRS. El análisis estadístico incluyó estadísticas descriptivas, pruebas de chi-cuadrado, pruebas de Kruskal-Wallis y modelos de regresión lineal multivariante con el objetivo de identificar factores asociados. Resultados: El estudio involucró a 164 pacientes, y la atresia pulmonar y ductus arterioso siendo diagnósticos comunes. La actividad física y la escolarización se vieron significativamente afectadas, con puntuaciones medianas de 32,14 (IR 17,14–62,87) y 56 (IR 28 - 88), respectivamente. El estado emocional y la actividad social mostraron mejores resultados, con puntuaciones medianas de 62 (IR 32–74) y 68 (IR 44–100), respectivamente. El diagnóstico de ventrículo único y la atresia pulmonar se asociaron con puntuaciones más bajas de calidad de vida en el estado emocional (p = 0,035) y la función física (p = 0.048), respectivamente. Conclusión: Este estudio subraya los desafíos continuos en la evaluación de la CVRS para niños con CC. Destaca asociaciones significativas entre diagnósticos específicos y puntuaciones disminuidas de CVRS, enfatizando la necesidad de estrategias de atención integral.